2022
DOI: 10.3390/diagnostics12020351
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Meningioma in Elderly Patients. Retrospective Multicentric Risk and Surgical Factors Study of Morbidity and Mortality

Abstract: With the increasing life expectancy, a large number of intracranial meningiomas (IM) have been identified in elderly patients. There is no general consensus regarding the management for IMs nor studies regarding the outcome of older patients undergoing meningioma surgery. We aimed to determine whether preoperative variables and postoperative clinical outcomes differ between age groups after meningioma surgery. We analyzed data from all patients who had undergone IM surgery from our departments. The final cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…We performed a multi-variate analysis comparing these data with grading and location; just a weak association ( p = 0.17) between edema volume and grading is shown for both groups ( Figure 6 ) and, analyzing the edema volumes among the different localizations of all meningiomas of this series, there is a variability among the different groups of meningiomas (ANOVA test, p = 0.04), with a prevalence of edematous lesions in meningiomas of the olfactory shower and sphenoidal plenum, without, however, substantial significance (p = 0.659, group 6, p = 1, group 11). In conclusion, there are no significantly edematous locations compared to others, but in medium/large meningiomas, as well as in the whole collection, there is no site more edematous than another, while in GIMs there is a mild correlation with the site of implantation as far as tumors of the anterior basicranium (olfactory shower and sphenoidal plenum) are concerned (this aspect will be evaluated in a further and dedicated study [ 35 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a multi-variate analysis comparing these data with grading and location; just a weak association ( p = 0.17) between edema volume and grading is shown for both groups ( Figure 6 ) and, analyzing the edema volumes among the different localizations of all meningiomas of this series, there is a variability among the different groups of meningiomas (ANOVA test, p = 0.04), with a prevalence of edematous lesions in meningiomas of the olfactory shower and sphenoidal plenum, without, however, substantial significance (p = 0.659, group 6, p = 1, group 11). In conclusion, there are no significantly edematous locations compared to others, but in medium/large meningiomas, as well as in the whole collection, there is no site more edematous than another, while in GIMs there is a mild correlation with the site of implantation as far as tumors of the anterior basicranium (olfactory shower and sphenoidal plenum) are concerned (this aspect will be evaluated in a further and dedicated study [ 35 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Once obtaining a volumetric ROI of the tumor mass ( Figure 2 ), with a simple arithmetic subtraction between these two volumes we obtained the value in cm 3 of the perilesional edema of the tumor [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…PBE originates in the margin regions of the tumor, suggesting a vasogenic origin and a pathogenic mechanism that primarily links IMs with BBB disorders; alternatively, the disruption of BBB is supposedly linked to the development of brain edemas in different conditions [15,16] From a biological point of view, no data was found to be associated with the development of IM with a high proportion of PBE [18]. Although previous studies reported that angiomatous and meningothelial types tend to be associated with more significant brain edemas [19], it was not possible to confirm such a clear association in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…We propose three possible explanations for this finding. Firstly, an increased BBB permeability could be associated with an increased vascular supply to the surgical cavity [19,22] during the post-surgical phase and may increase the risk of recurrence or regrowth in predisposed subjects. The presence of edemas suggests a greater predisposition to recur independently of the patient's grading, Ki-67 expression, and hormonal receptor status.…”
Section: Discussionmentioning
confidence: 99%
“…If, on the one hand, the advancements in the diagnostic and therapeutic tools over the years allow for better management of meningioma patients, resulting in a progressive improvement of the overall survival [ 14 , 15 , 16 ], on the other hand, the extension of life expectancy inexorably increases the risk of recurrence [ 5 ], which should be considered during the decision-making process of the strategy for treatment, as well as during the follow-up [ 5 ].…”
Section: Introductionmentioning
confidence: 99%